(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Over 20 years, there has been an explosive growth of interest in the application of Integrated Water Resource Management among majority of developing and developed countries in settling various type of water issue. Unfortunately, the effective implementation of this approach still remains in doubt. Fragmented water resources legislation, complexity of constitutional framework on water resources management, lack of coordination among stakeholders and overlapping of authorities in managing water resources are among the issues that challenge the Integrated Water Resource Management implementation. Therefore, this paper attempts to review the broad literature regarding what is still wrong with this approach and propose the solution on how to enhance the current implementation. Since, there is still no authorized framework available to be used by the stakeholders involved in assessing land use practice and comparing the effectiveness of the implementation progress between states in Malaysia, this paper briefly concludes that there is a need to develop a framework for Land Use Assessment as a work performance guideline especially to the various stakeholders involved. Therefore, it is hope that this finding would offer better improvement to water resource management through effective, good governance and practical ways.